Students' English Learning Style in Lubuklinggau - Yulfi Yulfi; Syaprizal Syaprizal (Linguistic, English Education and Art (LEEA) Journal, 2022)
This research aimed to explain the students' English learning style of eighth-grade students of MTs Negeri 1 Lubuklinggau. The method applied in this research was the descriptive quantitative method. All the eighth-grade students of MTs Negeri 1 Lubuklinggau in the academic year of 2018/2019 were this research's subject. The population was 244 students. Whiles sample of this research was taken by using simple random sampling. There were 30 students in class VIII as the sample result. To get the data, the researcher used a questionnaire and interview. The data were analyzed by describing students' answers and dividing students' English learning styles into three categories: 1) Visual Learning Style, 2) Auditory Learning Style, and 3) Kinesthetic Learning Style. Based on the result of data analysis, the researchers found that: 1) 10 (33.33%) students as visual learners, 2) 13 (43.33%) students as auditory learners, and 3) 7 (23.33%%) students as kinesthetic learners. In conclusion, the auditory learning style was the most frequently used style by the students. Whereas the least frequently learning style used by VIII.6 class of MTs Negeri 1 Lubuklinggau was kinesthetic. Keywords: English, Learning style, Students.